KOORDINASI ANTARA PEMERINTAH PUSAT DAN DAERAH DALAM UPAYA PROSES PENEGASAN BATAS ANTARA KABUPATEN MERAUKE DENGAN KABUPATEN BOVEN DIGOEL PROVINSI PAPUA - Ana Maisyaroh Indrayanti; Amy Yayuk Sri Rahayu (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2021)
Since the reform process began in 1998, there has been a previously centralistic change of the system towards decentralization. With this principle, the authority of the central government partly began to be handed over to the local government with the principle of regional autonomy. The region has the authority to organize its own household with the aim to be able to develop the potential of the area owned. This principle opens the need for the region to expand the region by dismantling the New Autonomous Region (DOB). However, after the formation of DOB began to arise problems related to the affirmation of unfinished regional boundaries. In its rules 5 years after the Regional Formation Law was established, the regional boundaries must be completed immediately, but in reality many exceed more than 5 years. This is due to the conflict of interest from each region so that a coordination is needed between the central and regional governments in the efforts of the boundary affirmation process in Indonesia. One example that can be raised is the Boundary Between Merauke Regency and Boven Digoel district of Papua Province. The success of this coordination process requires a firm commitment from the stakeholders involved in it. In addition, the Central Government (Minister of Home Affairs) who applies as a leader (leader) must also be able to influence others; motivating others; provide accurate information; And be able to make wise decisions